Mental health service users' experiences of psychiatric re-hospitalisation - an explorative focus group study in six European countries - M. Ådnanes; L. Melby; J. Cresswell-Smith; H. Westerlund; L. Rabbi; M. Z. Dernovšek; L. Šprah; R. Sfetcu; C. Straßmayr; V. Donisi (BMC, 2018)
Abstract Background Psychiatric re-hospitalisation is considered costly and disruptive to individuals. The perspective of the mental health service user is largely unexplored in literature. The purpose of our study was to explore service users' experiences of psychiatric re-hospitalisation across six countries in Europe. Method Eight focus groups were conducted in Romania, Slovenia, Finland, Italy, Austria and Norway. Results A total of 55 service users participated in the study. All participants had been in receipt of mental health services for at least 1 year, and had experienced more than one psychiatric hospitalisation. The experience of re-hospitalisation was considered: (1) less traumatising than the first hospitalisation, (2) to be necessary, and a relief, (3) occurring by default and without progress, (4) part of the recovery process. Conclusions Psychiatric re-hospitalisation was considered inevitable by the study participants, in both positive and negative terms. Striking similarities in service user experiences were found across all of the six countries, the first experience of psychiatric hospitalisation emerging as especially significant. Findings indicate the need for further action in order to develop more recovery and person-centred approaches within hospital care. For psychiatric inpatient care to be a positive part of the recovery process, further knowledge on what therapeutic action during the hospital stay would be beneficial, such as therapy, activities and integration with other services.